Perbandingan Kadar SGPT Pada Sampel Serum Darah Yang Segera Diperiksa Dengan Ditunda Selama 24 Jam dan 48 Jam Pada Suhu Ruang - Nurhidayanti Nurhidayanti; Denny Juraijin; Indah Setiani (Indobiosains, 2023)
Serum Glutamic Pyruvic Transaminase (SGPT) examination is an examination to determine the presence of disturbances in liver function. The SGPT enzyme is often used as an enzyme screening of basic parameter for a diagnosis and follow-up of disorders liver function. The types of specimens were used for SGPT examinations were serum, plasma heparin ora EDTA, and this study used serum samples. This study aimsto determine whether there are differences between the examination of SGPT levels which are immediately examined of postponed for 24 hours and 48 hours. This research is a cross sectional research with Posttest Only Control Group Design. This research was conducted at the Palembang Health Laboratory Center (BBLK) of South Sumatra Province on 28-30 December 2021 with the respondents of Diploma Medical Laboratory Technology Students level 2 and 3 with 30 samples. The results showed that the average SGPT level which immediately checked was 0.14, the average SGPT level delayed 24 hours was 0.13 and the SGPT level delayed 48 hours was 0.11. the results of the Two Way ANOVA test showed p value < 0,05, so it can be concluded that there was a change in the level of SGPT which immediately examined by being delayed for 24 hours and 48 hours at roon temperature